2021
DOI: 10.1111/jcmm.16500
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA‐302c‐3p inhibits endothelial cell pyroptosis via directly targeting NOD‐, LRR‐ and pyrin domain‐containing protein 3 in atherosclerosis

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 68 publications
(78 reference statements)
1
15
0
Order By: Relevance
“…In recent years, the roles of non‐coding RNAs (ncRNAs), including microRNAs, long non‐coding (lnc) RNAs and circulating (circ) RNAs, in disease pathogenesis, regulatory mechanisms and therapeutic applications have gradually become hot areas of research 90‐93 . Moreover, ncRNA has been shown to have an important regulatory role in CVD, 92,94‐105 tumours, 106 inflammation, 103,107 and heart development 108,109 . Increasing studies have shown that ncRNAs constitute potentially important players in biological regulation 110 .…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…In recent years, the roles of non‐coding RNAs (ncRNAs), including microRNAs, long non‐coding (lnc) RNAs and circulating (circ) RNAs, in disease pathogenesis, regulatory mechanisms and therapeutic applications have gradually become hot areas of research 90‐93 . Moreover, ncRNA has been shown to have an important regulatory role in CVD, 92,94‐105 tumours, 106 inflammation, 103,107 and heart development 108,109 . Increasing studies have shown that ncRNAs constitute potentially important players in biological regulation 110 .…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…The endothelium plays a pivotal role in the progression of AS and its complications, and endothelial dysfunction is widely recognized as one of the early alterations in the vessel wall preceding the development of plaques [24,25]. Emerging evidence has shown that the degree of endothelial cell (EC) apoptosis may be a key factor in the transition of a plaque from a stable state to a fragile state [26,27]. The glycolytic enzyme 6-phosphofructo-2-kinase/ fructose-2,6-biphosphatase (PFKFB3) is highly expressed in the ECs present in vulnerable human carotid atherosclerotic plaques, and inhibition of PFKFB3 activity reduces cell apoptosis in plaques and promotes plaque stability [28].…”
Section: Endothelial Cellsmentioning
confidence: 99%
“… 1 , 2 , 3 The disease is characterized by deposition of lipid and other blood components in the intima of the artery, proliferation of smooth muscle cells and increase of collagen fibres, chronic inflammation, plaque formation and hardening of the vascular walls. 3 , 4 , 5 The development of atheromatous plaques leads to serious clinical outcomes. 6 , 7 Once the vulnerable plaques rupture, they induce several clinical conditions, including stroke and myocardial infarction.…”
Section: Introductionmentioning
confidence: 99%
“…
Atherosclerosis (AS), one of the most common cardiovascular diseases, is the primary cause of morbidity and mortality in the case of cardiac events, thus posing a great threat to human health worldwide. [1][2][3] The disease is characterized by deposition of lipid and other blood components in the intima of the artery, proliferation of smooth muscle cells and increase of collagen fibres, chronic inflammation, plaque formation and hardening of the vascular walls. [3][4][5] The development of atheromatous plaques leads to serious clinical outcomes.
…”
mentioning
confidence: 99%